Aplikasi Sistem Peringatan Dini Pada Kebocoran Gas Dan Asap Menggunakan Sensor Gas MQ-7 Dengan Program C - Aan Burhanudin (Jurnal Informatika Upgris, 2016)
Abstract - Health Safety and Environment (HSE) in the development will be more accentuate on the prevention of occupational accidents and occupational diseases by identifying the potential to cause accidents and occupational diseases as well as anticipatory measures in case of accidents and occupational diseases. The working environment is directly in contact with toxic materials would be very harmful to the human body when exposed continuously. An environment or factory containing toxic gases as an example of CO, SO or LPG gas in certain concentrations can cause eye irritation or shortness of breath. Therefore we need an early warning system that can measure the concentration of these gases and may give a warning to workers associated with the concentration of the gas to the workers. The early warning system was made using three gas sensors, three heat sensors, LEDs and buzzer. Recitation and processing of the sensor is processed by a 16 bit microcontroller which will condition the room. In making such a system is used programmable fuzzy algorithms previously simulated with MATLAB, C Programming used as logic programming refers to the simulation results, miniature rooms created with three main space for workers in a hallway and an emergency exit. The results of such a system is in a room when the detected gas concentration exceeds the threshold, the system will activate the buzzer and will activated LED as the safest evacuation route directions. Keyword -- C Proframming, Fuzzy Logic, Matlab